Changes in New Zealand's Production Structure: An Input Output Analysis - Iris Claus (New Zealand Government, The Treasury, 2003)
This paper investigates changes in the production structure of the New Zealand economy using input output data. The analysis is undertaken at the 25-industry level using inter industry transactions for 1971-72, 1977-78, 1981-82, 1986-87, 1990-91 and 1994-95. Changes in the composition of gross output and value added are examined. Backward and forward linkages, indices of industry interconnectedness, a value added production multiplier, a cumulated primary input coefficient for compensation of employees and a measure of import content of final demand output are calculated, taking into account both direct and indirect transactions. The results suggest that some industries have been subject to large structural change and that a shift in New Zealand's pattern of industrial activity has occurred. These changes will have affected the transmission and propagation of shocks in the economy.
Keywords: C67; L16; 330; Input output models; industry importance; production structure; inter industry dependencies